Self-Reported Dysphagia and Laryngopharyngeal Reflux among a Community-Dwelling Elderly Rural Population - Sideris, Giorgos; Kourklidou, Melina; Plioutas, John; Georgantis, Ilias; Petridou, Eleni; Delides, Alexander (International Archives of Otorhinolaryngology, 2025)
There is a lack of community-dwelling population-based examinations of geriatric dysphagia and laryngopharyngeal reflux (LPR).To assess the prevalence of geriatric dysphagia and laryngopharyngeal reflux (LPR) in a community-dwelling population from a rural area.Volunteers from Velestino, a 4,000-person community, were given the Eating Assessment Tool (EAT-10) and Reflux Symptom Index (RSI) questionnaires at the health center. Demographic, medical, and pharmaceutical histories were recorded.160 participants (92 females, 68 males) self-presented. Ages were between 65–95 years (Mean 76.04). 27 (16.88%) scored an abnormal EAT-10 and 13 (8.13%) RSI over 13. RSI was statistically correlated with total and positive only EAT-10 scores. Age and gender did not affect EAT-10 or RSI scores. The EAT-10 score decreased with age progression.This is one of the few studies to investigate the relationship between geriatric dysphagia and LPR in a rural population. A 23.0% prevalence of dysphagia was observed in elderly adults as well as an increase in both EAT-10 and RSI scores with age progression. More studies are needed to explore this field.
Keywords: dysphagia; laryngopharyngeal reflux; epidemiology; elderly